The Implementation Analysis of SMEs Soundness Assessment Measurement for Service Industry in Bandung, Indonesia - Fatris, Evin Kartina; Sukarno, Subiakto (Journal of Business and Management, 2015)
Abstract-Soundness assessment is important for to know how effective the companyâ€™s performance in achieving the vision and objectives. With the similar sectors, the soundness level analysis classified in 2 categories that are the category company with bank-loan and the category of company without bank-loan. SMEs Soundness Assessment Measurement is the first SME Soundness measurement developed by Raden Roro Mirna and Subiakto Soekarno. In measuring SMEsâ€™ soundness, there are two aspect required that are financial and nonfinancial aspect. (Soundness Assessment Measurement Development for Indonesia Small and Medium Enterprises, 2014). The samples obtained are 15 service industry companies that consist of 9 companies with bank-loan and 6 companies without bank-loan. The sampleâ€™s assessment result will be compared using Independent Sample T-test with confidence level (Î±) 0.05. From the result shows that the sample group with bank-loan has 2 companies obtain â€œGood Soundness Iâ€ with rating AAA and the other 7 companies obtain â€œGood Soundness IIâ€ with rating AA. The sample group without bank-loan results 2 companies obtain â€œGood Soundness IIâ€ with rating AA and 4 companies obtain â€œFair Soundness Iâ€ with rating BBB. Based on the Independent T-test results there is no significant difference in financial aspect mean between company with loans and without loans that statistically proven by p > 0.05. While based on nonfinancial aspect, there is a significant difference in mean between companies with bank-loan and without bank-loan that statistically proven by p < 0.05.Â Keyword: small business, service Industry Company, bank-loan, SME Soundness Assessment Measurement, financial, nonfinancial.